Tamlana fucoidanivorans sp. nov., isolated from algae collected in China. Issue 3 (21st November 2019) - Li, Jin; Xu, Yan; Feng, Jiarong; Zhong, Mingqi; Xie, Qingyi; Peng, Tao; Hu, Zhong
Abstract : A Gram-stain-negative, aerobic, non-motile and rod-shaped marine bacterium, CW2-9 T, was isolated from algae collected from Fujian Province in PR China. 16S rRNA gene sequence analysis showed that this strain was affiliated with the genus Tamlana in the family Flavobacteriaceae of the class Flavobacteriia and was very similar to the type strain Tamlana sedimentorum MCCC 1A10799 T (96.3 % sequence similarity). The whole genome of strain CW2-9 T comprised 3 997 513 bp with a G+C content of 34.3 mol%. The average nucleotide identity value between strain CW2-9 T and T. sedimentorum MCCC 1A10799 T was 73.8 %. Growth was observed from 15 to 40 °C (optimum, 30 °C), at pH from pH 5.0 to 10.0 (pH 8.0) and in the presence of 0–4 % (w/v) NaCl (0–1 %). The major fatty acids (>10 % of the total) were iso-C15 : 0, iso G-C15 : 1, iso-C17 : 0 3-OH and anteiso-C15 : 0 . The predominant menaquinone was MK-6. The combined phylogenetic, physiological and chemotaxonomic data indicate that strain CW2-9 T represents a novel species in the genus Tamlana, for which the name Tamlana fucoidanivorans sp. nov. is proposed. The type strain is CW2-9 T (=CICC 24749 T =KCTC 72389 T ).